Investigation of reactions of Aryl Triazene/Diazene and their application for synthesis of Arylboronic esters and Diazaheterocycles - Zhu, Chuan (2013)
1-Aryltriazene and 1,2-diaryldiazene are important organic compounds not only for their biological or physical activities, but also for their synthetic applications. They are widely used as building block in heterocycle synthesis and coupling reactions for containing the unique N=N double bond. Thus the author started a research on these two kind of interesting compounds. In this Ph.D thesis, an investigation of the reaction of 1-aryltriazenes and 1,2-diaryldiazenes and their applications in organic synthesis is described. 1-Aryltriazenes are traditionally used as an equiverlant of aryldiazonium salt in the presence of a Brønsted or Lewis acid and could be applied to various nucleophilic substitution reactions, such as halogenation, hydroxylation and hydrogenation. However, there are no known reports about the carbon−metal bond formation in this kind of transformation, for example, creating a carbon−boron bond. At first the author focused on the reactivity of 1- aryltriazenes toward boron reagents. The author found 1-aryltriazene could be converted into the corresponding arylboronic ester via the deaminoborylation with B2pin2 mediated by BF3•OEt2.